NOVEL WAY OF DETERMINING SUM OF KTH POWERS OF NATURAL NUMBERS - Kumar, V.R. Kalyan; Sivaraman, R. (International Journal of Research -GRANTHAALAYAH, 2024)
Since ancient times, mathematicians across the world have worked on different methods to find the sum of powers of natural numbers. In this paper, we are going to present the relationship between sum of kth powers of natural numbers and sum of (k–1) th powers of natural numbers using the differential operator and associated recurrence relation. Interestingly, the Bernoulli numbers which occur frequently in mathematical analysis, play an important role in establishing this relationship.